Resistência camponesa no contexto da agricultura capitalista em Campo Verde – MT - Costa, Dehbora Alves da (2017)
In order to analyze peasantry resistance in Brazil, is necessary to understand a priori the contradictory process of development of capitalism in the Brazilian countryside, which, in its development, brought within it the reproduction of non-capitalist relations of production, a fact that explains the existence and permanence Of the peasantry in the country. This current of thought defends the creation and recreation of the peasantry within the capitalist relations, so that there is a growth of both the peasantry and the latifundia, a dialectical process that constitutes the agrarian reality of the state of Mato Grosso. The modern capitalist state plays a central role in the production of rural space and the expanded reproduction of capital, revealing in its interior the contradictions and conflicts derived from the class struggle, yielding now yes, but not strategically to the confrontation of the workers' struggle in the countryside , Mediating the conflicts between classes, but for the interests of the ruling class, unless pressed by mass organizations. The aim of the present research is to analyze peasant resistance in the context of modernized capitalist production relations in the set of state actions, seeing it as the director of capitalist relations in the countryside and, at the same time, mediator of the existing conflicts of struggle for the land. The methodology was qualitative, involving a bibliographical review, search for secondary data and, mainly, fieldwork, in which the elements of the text were studied from the reality itself and from the speeches collected. Mental maps were elaborated by some settlers representing their processes of experiences and experiences. As part of the results, it was observed that the peasants settled in the 14 de Agosto Settlement, from Campo Verde / MT, present a rich historical process of struggles and resistances until the consolidation of the settlement. The daily forms of resistance are diverse, such as peasant production, family labor, accessory work, leases and capitalist insertion in the territory of the settlement, which despite the contradictions are (re) created in the form of non-capitalist relations to reproduce As a class within capitalism. But, they still point out several challenges in relation to the generation of income that they deem necessary for the reproduction of life in the settlement.